A Low-cost Pitot Tube-based Experimental Model for Active Teaching-learning of Applied Fluid Mechanics: A Demonstration from NTTU - Chau, Than; Nguyen, Huong; Ly, Hung; Ghazali, Ihwan; Nguyen, Duy; Nguyen, Tho (Engineering Science Letter, 2023)
Using hands-on experiments in the classroom is a highly effective way to deepen students' understanding of theoretical concepts. By researching and developing a practical and cost-effective experiment using a pitot tube, we can transform the teaching of fluid mechanics from a content-based approach to one that promotes competency and practical application. The research includes exploring pitot tube theory, developing and evaluating the experimental design, simulating flow through the designed pitot tube using computational fluid dynamics simulation software, and implementing and evaluating learner satisfaction. The feedback we received from the students showed high satisfaction with the practical equipment used in the classroom and confirmed that this hands-on approach helped them achieve their learning objectives.